Streamlining one-dose package-handling process improves operational efficiency when dispensing drugs: A retrospective study - Takahiro Kato; Miki Kato; Kazuyo Nagashiba; Masayuki Takeuchi; Masafumi Onishi (Exploratory Research in Clinical and Social Pharmacy, 2025)
Background: Japanese pharmacists aim to improve efficiency and communication by simplifying work processes and developing protocols. While assistants and robots have been shown to improve drug dispensing, reports on the efficiency of pharmacies with automated dispensing systems are limited. This study explores factors affecting pharmacist efficiency in dispensing. Methods: 77Daily reports from our hospital pharmacy (December 1, 2020–November 30, 2021) were retrospectively analyzed. The primary outcome was the mean duration of drug dispensing. Multiple regression analyses identified factors affecting dispensing time. Strategies to address these factors were implemented, and outcomes were evaluated using data from December 1, 2021–November 30, 2022. Results: Univariate analysis identified that the prescription/pharmacist ratio, number of one-dose package (ODP) prescriptions, and powdered drugs significantly influenced dispensing time. Multivariate analysis confirmed that the prescription/pharmacist ratio (p < 0.001), ODP prescriptions (p < 0.001), and powdered drugs (p = 0.02) were key factors. A higher number of ODP prescriptions generally increased dispensing time. After implementing a new strategy for checking ODP, mean dispensing time decreased from 20.0 ± 4.0 to 18.5 ± 3.6 min (p < 0.001), and the percentage of tasks completed in under 20 min increased from 56.3 % to 73.6 % (p < 0.001). Dispensing times were reduced without changing staffing levels by reallocating tasks. Conclusions: Optimizing the ODP verification workflow enhances dispensing efficiency without increasing pharmacist workload, highlighting the importance of prioritizing ODP prescriptions and implementing support tools for final checks, while further multicenter studies are needed to confirm these findings across diverse settings.